Efficacy of Melatonin Administration in Reducing Headaches in Children with Migraines without Sleep Disorders: 1. Simin Tahmasbi. Tahmas.s2004@gmail.com 09133814926 2. Fereshte Aein Email: fereshtehaein@yahoo.com 09131024581 - Tahmasbi, Simin; Aein, Fereshteh (Iranian Journal of Child Neurology, 2024)
Objectives Migraine is one of the common diseases of children, which can disrupt their quality of life. Some studies have shown the effect of melatonin in reducing migraine headaches. This study aims to investigate the effect of melatonin administration in reducing headaches in children with migraine without sleep disorders. Materials & Methods In this clinical trial study, fifty-five children aged five to 15 years with migraines who had no sleep disorder were enrolled. The control group (twenty-seven patients) was treated with propranolol tablets, and the intervention group (thirty patients) was treated with propranolol tablets plus melatonin tablets for three months. Patients were visited before, one month, and three months after the start of treatment, and their data was collected and recorded. Results The number of headache attacks decreased significantly in the intervention group compared to the control group three months after the treatment (P=0.006). The number of patients with a good response to treatment in the intervention group was significantly more than the control group (p=0.023). Parents’ satisfaction with the treatment in the intervention group was significantly higher than the control group (P=0.026). There was no significant difference in the intensity of disability caused by headaches after treatment in the two groups. No significant drug side effects were seen in any of the two groups. Conclusion Adding melatonin to the treatment of children with migraine without sleep disorders significantly reduces the frequency of headache attacks and increases satisfaction with the treatment